2006
DOI: 10.1021/op060033k
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies of the Asymmetric Transfer Hydrogenation of Imines with Formic Acid Catalyzed by Rh−Diamine Catalysts

Abstract: Kinetic studies of the asymmetric transfer hydrogenation of imines with HCOOH using Rh-chiral diamine catalysts reveal anomalous concentration dependences attributed to the participation of both reactant and product in the formation of formate salts. The resting state of the catalyst is suggested to be the Rh hydride species 5. The role of bases such as Et 3 N in metering HCOOH into the catalytic cycle is discussed. A practical reaction protocol for achieving high productivity based on slow addition of HCOOH i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 10 publications
3
43
0
Order By: Relevance
“…The catalysts gave high ee values for the reduction of 1-alkyl-3,4-dihydroisoquinolines (entry 3) and moderate ee values for that of benzoisothiazole dioxides (entry 2), but struggled to induce any enantioselectivity when reducing 1-aryl-3,4-dihydroisoquinolines (entry 4) or acyclic imines (entry 1). Blackmond and coworkers performed a kinetic analysis of this catalyst system and showed that its activity could be further improved by the slow addition of HCO 2 H [173]. a) Conversion to and ee of amine product.…”
Section: Asymmetric Transfer Hydrogenation Of Iminesmentioning
confidence: 99%
“…The catalysts gave high ee values for the reduction of 1-alkyl-3,4-dihydroisoquinolines (entry 3) and moderate ee values for that of benzoisothiazole dioxides (entry 2), but struggled to induce any enantioselectivity when reducing 1-aryl-3,4-dihydroisoquinolines (entry 4) or acyclic imines (entry 1). Blackmond and coworkers performed a kinetic analysis of this catalyst system and showed that its activity could be further improved by the slow addition of HCO 2 H [173]. a) Conversion to and ee of amine product.…”
Section: Asymmetric Transfer Hydrogenation Of Iminesmentioning
confidence: 99%
“…Recent kinetic studies have been carried out on the Rh(III) catalyst system by Blackmond [22,23] which have served to shed further light on the mechanism of the reduction of imines. The study revealed that the resting state of the catalyst was as the Rh -hydride species, that is, where the chloride of the " precatalyst " is replaced by a hydride.…”
Section: Organometallic Catalysts Based On Ru Rh and Irmentioning
confidence: 99%
“…The study revealed that the resting state of the catalyst was as the Rh -hydride species, that is, where the chloride of the " precatalyst " is replaced by a hydride. The successful operation of the catalyst is shown to depend upon the acid -base equilibria, and this observation has led to a highly valuable, improved experimental protocol in which formic acid is added slowly to the solution rather than as a single dose at the start [22] . The observed importance of the solution pH mirrors Xiao ' s observations in the aqueous ketone reduction process [24] .…”
Section: Organometallic Catalysts Based On Ru Rh and Irmentioning
confidence: 99%
“…This information can be used for fundamental mechanism study, 1,2 reaction kinetic investigation [3][4][5] and process control. [6][7][8][9] As for mid-IR monitoring of some less complicated reactions, calibration using a single frequency or the ratio of two frequencies has been proved adequate to obtain concentration profiles.…”
Section: Introductionmentioning
confidence: 99%